Mapping intervention strategies and mental health support journeys in addressing mental health challenges among healthcare professionals – a scoping review - Siphesihle Khanya Mahanjana; Lerato Anna Pitso; Mhlengi Vella Ncube (BMC Psychology)
Abstract Background Mental health conditions can cause severe morbidity and mortality, especially if left untreated. The prevalence of mental illness among healthcare workers (HCWs) is growing and concerning. Compared with the general population, HCWs are at greater risk of developing mental illnesses such as depression and anxiety. Healthcare systems need to promote the mental health and well-being of HCWs using evidence-based interventions. This scoping review aimed to synthesise evidence that describes strategies and interventions that promote mental health and prevent mental illness among HCWs. Methods An electronic search of Google Scholar, CINAHL Ultimate, Dentistry & Oral Sciences Source, and MEDLINE Ultimate databases was conducted. The search targeted peer-reviewed academic literature reporting on primary data from January 2020 to June 2023. Studies that reported on mental health interventions for clinical healthcare workers and the outcomes of the interventions were included. Results Eleven studies met the inclusion criteria. The majority (78.8%) of mental health interventions were designed for nurses, with medical doctors and allied health professionals representing only 4.1% and 9.5% of the healthcare worker population in the studies respectively. The interventions described in the studies varied and included psychoeducation and education, psychotherapy, physical activity, resilience interventions, well-being centres, and a video intervention. All the interventions followed a similar implementation process, which is described in a mental health support journey map. The map included the following activities: enrolment, information session, accessing educational resources, mental health intervention, accessing human resources, and group support. The studies reported on thirty different outcome measures, with the most common being overall mental well-being, anxiety, insomnia/sleep quality, depression/depressive symptoms, and psychological distress. Conclusion Mental health interventions for HCWs enhance overall well-being. Physical activity, resilience-building, psychoeducation, and tailored digital tools are effective intervention strategies to improve the mental health of healthcare workers. Resource allocation towards these mental health intervention strategies for healthcare workers needs to be included in the operational budgets of healthcare establishments. Further studies may be required to customise some of the interventions for low- and middle-income countries.